Phosphorus dynamics and sustainable agriculture: The role of microbial solubilization and innovations in nutrient management - José Abraham García-Berumen; Juan Armando Flores de la Torre; Sergio de los Santos-Villalobos; Alejandro Espinoza-Canales; Francisco Guadalupe Echavarría-Cháirez; Héctor Gutiérrez-Bañuelos (Current Research in Microbial Sciences)
Phosphorus (P) is an essential element for plant growth, playing a crucial role in various metabolic processes. Despite its importance, phosphorus availability in soils is often restricted due to its tendency to form insoluble complexes, limiting plant uptake. The increasing demand for phosphorus in agriculture, combined with limited global reserves of phosphate rock, has created challenges for sustainable plant production. Additionally, the overuse of chemical phosphorus fertilizers has resulted in environmental degradation, such as eutrophication of water bodies. Increasing agronomic phosphorus (P) efficiency is crucial because of population growth and increased food demand. Hence, microorganisms involved in the P cycle are a promising biotechnological strategy that has gained global interest in recent decades. Microorganisms' solubilization of phosphate rock (PR) is an environmentally sustainable alternative to chemical processing for producing phosphate fertilizers. Phosphorus-solubilizing microorganisms (PSMs), including bacteria and fungi, and their enzymatic processes offer an eco-friendly and sustainable alternative to chemical inputs by converting insoluble phosphorus into forms readily available for plant uptake. Integrating PSMs into agricultural systems presents a promising strategy to reduce dependence on chemical fertilizers, enhance soil health, and contribute to the transition toward more sustainable and resilient agricultural practices. It can be an alternative that reduces the loss of phosphorus in the environment, especially the eutrophication of aquatic systems. This paper explores the challenges of phosphorus availability in agriculture and the potential of microbial phosphorus solubilization as a sustainable alternative to conventional practices.